2018
DOI: 10.1111/odi.12772
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the 2016 ACR‐EULAR and the 2002 AECG classification criteria for Sjögren's syndrome: Findings from the NIH cohort

Abstract: There was high agreement between the two classification sets with comparable performance diagnostics. There was no evidence of superior performance value by the new 2016 ACR-EULAR set over the AECG set, and the two sets were found to be equivalent. Findings from our cohort indicate that 2016 ACR-EULAR classification could be extended to classification of sSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
1
14
0
7
Order By: Relevance
“…There is a high concordance between the previously published classification criteria and the 2016 ACR/EULAR criteria 2830 . However, an important change from older criteria is that the latest criteria give credit for the presence of an extraglandular manifestation.…”
Section: Selection Of Patients For Clinical Trialssupporting
confidence: 60%
“…There is a high concordance between the previously published classification criteria and the 2016 ACR/EULAR criteria 2830 . However, an important change from older criteria is that the latest criteria give credit for the presence of an extraglandular manifestation.…”
Section: Selection Of Patients For Clinical Trialssupporting
confidence: 60%
“…Subjects diagnosed with primary Sjögren's Syndrome (pSS) [18] were recruited through NIDCR Sjögren's…”
Section: Patient Population and Sampling Proceduresmentioning
confidence: 99%
“…60 These criteria were validated in cohort studies and showed a high level of agreement with earlier guidelines. [61][62][63][64]…”
Section: Clinical Featuresmentioning
confidence: 99%